Impact of inputs costs on farm profitability: an evaluation of pearl millet production in north-western Nigeria - Mukhtar, Umar; Mohamed, Zainal Abidin; Shamsuddin, Mad Nasir; Sharifuddin, Juwaidah (Asian Economic and Social Society, 2017)
The current study was carried out to estimate cost, returns and the profitability level of pearl millet production in north-western Nigeria. The study made use of primary data collected from a cross section of 430 pearl millet farmers and analysed using descriptive statistics, budgetary technique, profitability ratio, and Ordinary Least Square regression analysis. The study reveals that an average gross margin and net farm income across all the sampled pearl millet farms were $233.89 and $200.89 respectively, while average total cost was $ 229.35 per cultivation season. The profitability index, rate of return on investment and capital turnover were $ 0.43, 0.77 and $ 1.77, respectively. This is an indication that pearl millet production is profitable in the study area. It is also established that the coefficients of costs of renting land, fertilizer, labour, seed, agrochemicals and price of pearl millet output have significantly impact on gross margin of pearl millet production. Based on the above findings, the study concludes that profit level of the pearl millet can be significantly increased with policies that guarantee better farmer price and lower inputs costs.